Flexible Microstrip Patch Antenna Design on Jeans Substrate Radiating at 2.45 GHz for WBAN Application - Mulkalla, Saikumar; Fakirde, Avish; Peshwe, Paritosh D. (Progress in electromagnetics research M Pier M, 2023)
This study presents a compact, low-profile, and flexible fabric antenna specifically designed for on-body Wireless Body Area Networks operating within the Industrial, Scientific, and Medical (ISM) frequency band at a central frequency of 2.45 GHz. The proposed antenna employs a jeans substrate, with a dielectric constant [[epsilon].sub.r] = 1.67 and loss tangent tan [delta] = 0.025, which is 0.5 mm in thickness, allowing for its flexibility. The antenna incorporates slots on the patch and a Defected Ground Structure (DGS), with a total size of 36 x 55 x 0.6 m[m.sup.3] (0.29[[lambda].sub.o] x 0.45[[lambda].sub.o] x 0.005[[lambda].sub.o] m[m.sup.3]). To assess the antenna's flexibility, bending analysis was performed, while its performance was evaluated using a phantom model that simulates human tissue, comprising skin, fat, and bone, with respective thicknesses of 1 mm, 0.5 mm, and 4 mm. The final model of the antenna operates at a central frequency of 2.45 GHz, with an impressive bandwidth of 0.8 GHz. The proposed design maintains a high level of directivity, gain, and reflection coefficient ([S.sub.11]) at the desired frequency, with values of 4.7 dBi, 3.6 dBi, and -41 dB, respectively. The Specific Absorption Rate (SAR) of the final antenna was measured on the above model and found to be 0.114 W/Kg for 1 g of tissue, which is well within the limits established by IEEE and FCC standards. Both the measured and simulated values of return loss and gain suggest that the proposed antenna is eminently suitable for body-worn applications.